Esporte paralímpico: fatores motivacionais que influenciam a prática do atletismo - Souza, Roberto Sillas de Lima (2018)
The Paralympic Sport is an important sociocultural phenomenon in the 21st century. Athletics is officially present in the program of the Paralympic Games since its first edition in 1960. The modality offers several tests with different characteristics, allowing access to various types of deficiencies. The objective of the present study was to analyze the motivational factors that influence people with disabilities to participate in the practice of athletics. The study is characterized as qualitative descriptive. The sample consisted of twelve paratletas of both sexes, age group of 17 to 46 years. Sampling was non-probabilistic for convenience. The variables investigated were about the reasons that lead persons with disabilities to the initiation and the permanence of the athletics practice. He instrument used for data collection was the half structured interview. The data were analyzed qualitatively through the Bardin content analysis. The results revealed that the main reasons why athletes start in sports are: social influence, pleasure for practice and opportunity for recognition. The results also point out that the difficulties experienced when starting sports life are: the lack of financial incentive, public transportation and the place of training and equipment. And, the factors that motivate athletes to stay in the practice of the sport are the: results obtained, improve financial condition, family, love of sport, health maintenance and Paralympic dream.